FENOMENA DAN DETERMINAN KESEMPATAN ANAK MASUK DUNIA KERJA - Selli Nelonda (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2013)
In most countries including Indonesia, children are very valuable future human resources in development process; they are the future of a country. For these reasons all stakeholders have the equal obligation to promote opportunity for the children to get their basic needs for their better future. But, the reality is not always as good as it should be, for some reasons, there are many children still enter the labor market than being at school for their education. Using 2009 Susenas data with binary logistic regression model, this research find that parents education, parents marital status, parent jobs sector, economic sector activity, number of children in a household, share of food expenditure and geographic factor are the significant factors to determine the probability a child entering the labor market.